2008
DOI: 10.1016/j.ajhg.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic Profiling Reveals DNA-Methylation Changes Associated with Major Psychosis

Abstract: Epigenetic misregulation is consistent with various non-Mendelian features of schizophrenia and bipolar disorder. To date, however, few studies have investigated the role of DNA methylation in major psychosis, and none have taken a genome-wide epigenomic approach. In this study we used CpG-island microarrays to identify DNA-methylation changes in the frontal cortex and germline associated with schizophrenia and bipolar disorder. In the frontal cortex we find evidence for psychosis-associated DNA-methylation di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
527
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(564 citation statements)
references
References 63 publications
(79 reference statements)
26
527
2
9
Order By: Relevance
“…Disruption of epigenetic profile is a feature of most cancers (61)(62)(63) and is speculated to play a role in the etiology of other complex diseases (13,64,65), including asthma (66), allergy (67), obesity, type 2 diabetes, coronary heart disease, autism spectrum disorders (68), and bipolar disorder and schizophrenia (69)(70)(71)(72)(73). The potential to identify distinct epigenetic biomarkers associated with eating disorders has also been explored (74,75).…”
Section: Epigenetics and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of epigenetic profile is a feature of most cancers (61)(62)(63) and is speculated to play a role in the etiology of other complex diseases (13,64,65), including asthma (66), allergy (67), obesity, type 2 diabetes, coronary heart disease, autism spectrum disorders (68), and bipolar disorder and schizophrenia (69)(70)(71)(72)(73). The potential to identify distinct epigenetic biomarkers associated with eating disorders has also been explored (74,75).…”
Section: Epigenetics and Diseasementioning
confidence: 99%
“…These fractions can then be hybridized to DNA microarrays or sequenced en masse. Low-resolution array methodology has been used to identify genes consistently differentially methylated in a case-control study of psychosis (73) and has the potential to quickly (although not inexpensively) identify genes differentially methylated in a range of complex disorders in case-control studies.…”
Section: Measuring Epigenetic Profilementioning
confidence: 99%
“…Indeed, the G>A (Val>Met) substitution of the rs6265 SNP creates/abolishes a CpG site, so that the Val allele has a CpG at this position while the Met allele does not. Since this CpG is differentially methylated in humans, 36 we hypothesize that the epigenetic changes able to modulate the effect of rs6265 may correspond to a different methylation status of the Val allele in ValVals and ValMets. In other words, while in experimental models the rs6265 genotype is clearly associated with certain outcomes, in living people who experience actual life and its many stressors DNA methylation specifically of one allele of this SNP may change in response to those factors, such as hOCs, and may modulate specific phenotypes, thus weakening the effect of the rs6265 genotype.…”
Section: Introductionmentioning
confidence: 99%
“…These investigators found significant evidence for a 'modular structure' of the methylome (computed from correlated changes between promoters) from brain DNA recalling the genome-wide 'masking' function speculated by Rollins et al (2006) (Figure 3). Mill et al (2008) suggest that the normal mCpG modularity is degraded in the major psychoses, indicating fragmented or poorly communicating promoter nets. Of clinical interest, an abundance of independent gene loci were differentially methylated between controls and psychiatric patients, factored by gender.…”
Section: Studies In Psychiatric Subjectsmentioning
confidence: 99%
“…These investigators also show that higher methylation is significantly correlated to mRNA expression arguing that CpG methylation in neurons has functional consequences (Siegmund et al 2007). Mill et al (2008) likewise examined genomic DNA obtained from the frontal cortex of 125 brain samples from subjects with a diagnosis of schizophrenia, bipolar disorder, and non-psychiatric controls. DNA from these samples was enriched for the unmethylated fraction (containing CpG islands) using an enzymatic and PCR coupled method, and this enriched fraction was hybridized to a CpG island microarray.…”
Section: Studies In Psychiatric Subjectsmentioning
confidence: 99%